2013
DOI: 10.1021/tx4002868
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Perturbations Induced by Bacterial Infection Affect Arsenic Biotransformation

Abstract: Exposure to arsenic affects large human populations worldwide, and has been associated with a long list of human diseases, including skin, bladder, lung, and liver cancers, diabetes, and cardiovascular disorders. In addition, there are large individual differences in susceptibility to arsenic-induced diseases, which are frequently associated with different patterns of arsenic metabolism. Several underlying mechanisms, such as genetic polymorphisms and epigenetics, have been proposed, as these factors closely i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 67 publications
2
54
0
Order By: Relevance
“…Bioaccessiblity and bioavailability play a role in potential health effects from arsenic exposure. Most of the metabolism of arsenic is thought to take place in the liver, however, there is evidence that gut microbiome metabolism may also take place and could have a significant impact on absorption/excretion and associated health effects form arsenic exposure (60,86). Unmeasured bioaccessibility/bioavailability will increase the variation in our arsenic exposure estimates and when using the metabolite variables as outcomes we would have reduced power to detect associations with these exposure factors.…”
Section: Discussionmentioning
confidence: 99%
“…Bioaccessiblity and bioavailability play a role in potential health effects from arsenic exposure. Most of the metabolism of arsenic is thought to take place in the liver, however, there is evidence that gut microbiome metabolism may also take place and could have a significant impact on absorption/excretion and associated health effects form arsenic exposure (60,86). Unmeasured bioaccessibility/bioavailability will increase the variation in our arsenic exposure estimates and when using the metabolite variables as outcomes we would have reduced power to detect associations with these exposure factors.…”
Section: Discussionmentioning
confidence: 99%
“…10 Studies have clearly illustrated that gut microbiota significantly affect As metabolism by, for example, reduction, methylation, and thiolation. 11 As metabolism in contaminated soil by human gut microbiota can affect As bioaccessibility and speciation. 10,12 Therefore, As biotransformation must be considered an essential part of the risk assessment of oral soil As exposure using in vitro methods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As ( (Lu et al, 2013). The previous study showed that As(V) is the predominant form (nearly N99%) for the small intestinal digest in contaminated soils (Yin et al, 2015b).…”
Section: Tablementioning
confidence: 96%